THE RELATIONSHIP OF DESTINATION IMAGE, QUALITY OF TOURIST PRODUCT ATTRIBUTES, WORD OF MOUTH, ELECTRONIC WORD OF MOUTH (E-WOM) ON VISITING DECISIONS - Verinita Verinita; Rachmi Indrianti (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
This study aims to determine the effect of destination images, quality attributes of tourism products, word of mouth, electronic word of mouth (e-WOM) on the decision to visit Bukik Chi Nangkiak tourist destination, Solok Regency, West Sumatra Province. This type of research is an explanatory time horizon, with a quantitative approach. The sampling technique is purposive sampling with the criteria of respondents who have visited a tourist destination once and are 17 years old. The number of samples used in the study was 130 respondents. Data were analyzed using SPSS (Statistical Product and Service Solutions). The results revealed that the image of the destination, the quality of the attributes of tourism products, electronic word of mouth (e-wom) did not significantly influence the visiting decision. Likewise, the electronic word of mouth (e-wom) variable is not significant. Only the Word of Mouth variable has a significant effect on the decision to visit. This is an interesting finding because at present wom communication is no longer considered effective because the intensity of meetings between individuals is decreasing but the results of the study show a significant effect. Based on the results of the study it can be recommended that to improve the decision to visit a tourist destination an optimization of the use of communication technology is carried out. Through e-wom promotion activities such as Instagram, Facebook, Twitter, Whats App. This indicates that technological advances play a major role in promoting tourist destinations.